Tourist Arrivals And Economic Growth In Sarawak - Lau, Evan; Oh, Swee-Ling; Hu, Sing-Sing (MPRA, 2008)
This study empirically investigates the comovements and the causality relationship between tourist arrivals and economic growth in Sarawak during the period of 1972 to 2004. The empirical evidence clearly shows that the long run causality running from tourist arrivals to economic growth in the estimation period. As one of the income generator for Sarawak, the findings are consistent with economic theory and proffer important policy conclusions.